Proceedings of the OSCAR Workshop: Mechanized and efficient silviculture : November 25–26, 2015 Natural Resources Institute Finland, Suonenjoki Research Unit, Finland - (:unkn) unknown (Natural Resources Institute Finland (Luke), 2016)
The workshop took place at Natural Resources Institute Finland (Luke), Suonenjoki Research Unit November 25 – 26, 2015. Workshop was arranged as a joint arrangement between Luke and Latvian State Forest Research Institute "Silava" and the main sponsor was Nordic Forest Research (SNS) / Operating Systems for Centre of Advanced Research (OSCAR2, 2011-2015). This OSCAR Workshop was also promoted by IUFRO Research Group 3.02.00 Stand establishment and treatment. Altogether 28 participants from Estonia, Finland, Latvia, Lithuania and Sweden participated in the workshop. The objective of the workshop was to present ongoing research concerning mechanized silviculture in Nordic and Baltic countries and to discuss future research needs. State of art reports about mechanized silviculture from Sweden and Finland were presented and discussed. In the Swedish review, inverting; interface from nursery to planting machine; feeding of seedlings in planting device; identification of plantings spots and obstacles as well as planting device development without compactation were covered. In the Finnish part, mechanized planting and mechanized young stand management were discussed. Finally, the differences between the Swedish and Finnish Scots pine management cultures were discussed. The ongoing research projects concerning forest regeneration, drainage and management of young stands in Baltic countries were presented and discussed. The overview about the management of Latvia’s state forests started the session following the state of the art review of the ongoing research activities in mechanization of silviculture in Latvia. Next, the work productivity of wood ash forest fertilization was discovered. Forest regeneration and young stand management in Estonia followed. In conclusion, SeedPAD, as a new and efficient Scots pine regeneration method in Northern Sweden, was viewed. New ways of young stand management were presented and discussed. At first, the productivity of Vimek harvester and forwarder were scrutinized. Next, Fixteri FX15a small-tree bundlers work processes and productivity in early pine dominated thinnings were considered following an overview of the evolution of innovative systems for small diameter tree harvest in Sweden. In the end, biocontrol methods against hardwood sprouting using Chondrostereum purpureum were covered. In the workshop the need for further Nordic-Baltic co-operation was strongly emphasized. Cooperation in research activities as well as in dissemination of new research findings and in deployment of new innovation were widely discussed. Workshop included also a short field excursion where the PCT operation with “Tehojätkä” (Usewood Forest Master) and young stands treated with Naarva uprooter were demonstrated.
Keywords: silviculture; mechanization; direct seeding; planting; pre-commercial thinning; thinning